Supply Chain Management Information System Model for Electric Power Management in Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2022)
The paper aimed to design supply chain management information system model for electric power management in Thailand and an evaluation of the model. A Samples are ten experts in the field of information system and supply chain. The data is analysed by means and standardized deviations. The research result shows that the model consists of eight elements namely main components, seller Power plant generates electricity, Substation, Transmission, Substation, Power Lines and Customers. the assessment of model using Black-Box technique and the result shows the overall rating mean of 3.65 and standard deviation of 0.58, which means that the model is appropriate at the high level and can support an information system development.Â